Pengukuran Antarmuka Pengguna 3D Menggunakan Metode System Usability Scale pada Aplikasi Simulasi Videography Virtual Reality - Ady Purna Kurniawan; Rickman Roedavan; Asaas Putra; Sani Apriliani (Sekawan Institut, 2023)
The development of Virtual Reality (VR) technology has revolutionized user interaction with mobile applications. However, the success of a VR application depends on how well the user interface (UI) is implemented. Therefore, measuring the usability of the UI is necessary to ensure a satisfactory user experience. In measuring the quality of the user interface, we utilized the SUS (System Usability Scale) method, which is a standardized tool for assessing the user interface of a system. Our respondents consisted of 84 participants who had experience using VR applications. They were asked to use the application and complete a 10-statement SUS questionnaire with a Likert scale. Data analysis indicated that the average SUS score for the user interface of the VR videography simulation mobile application was 78.51. This score signifies that the VR Videography application's user interface received ratings of Passive, Acceptable, Good, and Grade B in their respective categories. These scores indicate that the user interface received positive evaluations from users. The questionnaire also revealed that the majority of respondents found the application easy to use and believed that others would also find it easy to comprehend